2013
DOI: 10.1186/1475-2867-13-48
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of PI3K/AKT pathway enhances sensitivity of Raji cells to chemotherapy through down-regulation of HSP70

Abstract: Up-regulation of heat shock protein 70 (HSP70) could be elicited primarily by heat in former studies, and this was proved to be associated with cancer progression. Burkitt's lymphoma is one of highly aggressive B-cell non-Hodgkin’s lymphoma and is one of the fastest growing human tumors. To investigate the effect of HSP70 expression on the sensitivity of human Burkitt lymphoma cells (Raji cells) to chemotherapy and its role in the involvement of PI3K/AKT pathway, we evaluated the effects of LY294002, a PI3K in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“…The elevated expression of HSP70 in clinical breast and endometrial cancer samples is associated with cancer progression and poor prognosis (13,14). Fang et al and He et al reported that HSP70 and HSP90 are associated with increased resistance to chemotherapy and may therefore be potential therapeutic targets in refractory malignancies (15,16). However, HSP70 inhibitors have high toxicity and do not exert tumor-specific effects (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated expression of HSP70 in clinical breast and endometrial cancer samples is associated with cancer progression and poor prognosis (13,14). Fang et al and He et al reported that HSP70 and HSP90 are associated with increased resistance to chemotherapy and may therefore be potential therapeutic targets in refractory malignancies (15,16). However, HSP70 inhibitors have high toxicity and do not exert tumor-specific effects (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous NO or preinduction of iNOS stimulates the HSP70 expression and subsequently prevents hepatocytes from tumor necrosis factor alpha (TNFa)-and actinomycin D-induced apoptosis (Kim et al, 1997). Blockade of the PI3K/AKT pathway enhances sensitivity of Raji cells to chemotherapy through the down-regulation of HSP70 (Fang et al, 2013). Treatment with SNAP induces HO-1 expression in rat glial cells (Kitamura et al, 1998), and HO-1 mediates the cytoprotective effects in microglia immunostimulated by lipopolysaccharide (LPS) (Lee and Suk, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study also indicated the existence of PI3K/Akt/HSP70 cascade in Raji cells lines [4]. LY294002 significantly attenuated Akt activation, resulted in induced cell apoptosis and increased ADM and DDP sensitivity [4]. PI-103, a dual PI3K/mTOR inhibitor, was also associated with the caspase-dependent cleavage of PARP and inhibition of c-MYC activity in BL cells [29].…”
Section: Introductionmentioning
confidence: 96%
“…In drug-resistant Ramos and Daudi B-NHL cell lines, LY294002 treatment also accounted for the inhibition of Bcl-(xL) expression and sensitization to drug-induced apoptosis [61]. Our previous study also indicated the existence of PI3K/Akt/HSP70 cascade in Raji cells lines [4]. LY294002 significantly attenuated Akt activation, resulted in induced cell apoptosis and increased ADM and DDP sensitivity [4].…”
Section: Introductionmentioning
confidence: 99%